2016
DOI: 10.1007/s10484-016-9333-1
|View full text |Cite
|
Sign up to set email alerts
|

A Stress Management Program for Higher Risk Medical Students: Preliminary Findings

Abstract: Approximately 10 % of first year medical students have clinically relevant anxiety or depression which may affect academic success and quality of life. This study tested the effects of a stress management intervention on indicators of anxiety, depression and self-efficacy in self-selected first year medical students. Forty two medical students volunteered to participate and provided informed consent. An eight session intervention was offered and focused on building relaxation skills, adaptive coping, and basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 14 publications
0
20
1
9
Order By: Relevance
“…Contrary to our expectations and previous studies, social support and self-efficacy are not improved after the participation in the program (130, 131). Self-efficacy is one the most important predictors of distress (25), but also an important personal resource to reduce the effects of stress in well-being (132), like social support (133, 134).…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our expectations and previous studies, social support and self-efficacy are not improved after the participation in the program (130, 131). Self-efficacy is one the most important predictors of distress (25), but also an important personal resource to reduce the effects of stress in well-being (132), like social support (133, 134).…”
Section: Discussioncontrasting
confidence: 99%
“…Brennan et al (2016) [54] and McGrady et al (2012) [56] propose that education and the development of certain skills at university leads to positive behavioral change of students. According to them, interventions should include awareness of breathing, muscle relaxation, coping skills, adequate nutrition, and positive psychology to overcome the problems arising from mental health [49].…”
Section: Discussionmentioning
confidence: 99%
“…Support strategies that had been assessed in other studies concluded the survey and represent the underlying data of this manuscript. Items (N = 22) were extracted to evaluate support options such as accessible counselors (Brennan et al 2016) or changing the grading system into a pass/fail system (Wasson et al 2016). The leading question was, "In order to better deal with my study-related stress, I would use the following services/wish the following services were offered."…”
Section: Instrumentsmentioning
confidence: 99%
“…According to our knowledge, no other survey has been published listing different options as rated by students. Normally, studies either consist of meta-analyses (Schmidt and Hansson 2018) or the assessment of a direct intervention (Brennan et al 2016). Qualitative collections of student suggestions exist, where a relatively small number of participants indicated options they preferred (Kötter et al 2015).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation